Pengembangan Media Poop Up Book Berbasis Problem Based Learning Kelas 1 Tema 7 Benda, Hewan dan Tanaman di Sekitarku - Dahlyyatun Asmy Dalimunte; Nurmairina Nurmairina (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This development research aims to (1) Develop poop up book media based on problem based learning on the theme of 7 objects, animals and plants around me (2) Find out the feasibility of poop up book learning media with a problem based learning model (3) To find out the teacher's response to poop up book learning media. The type of research model used in this research is the Research and Development (R&D) model. ADDIE development is a model that involves model development stages with five steps or five phases including: Analysis, Design, Develop, Implement and Evaluate. The subjects in this research were grade 1 students at SD IT Al-Furqon Lubuk Rotan, validators (media experts and material experts). The instrument used to collect data was a questionnaire. The data analysis technique used in this research is the Likert scale. Based on analysis of data obtained through validity tests of media experts, material experts, teacher responses and student responses. The validation results by media experts were 88.3%, including the Very Eligible category. The validation results by material experts were 83% in the Very Eligible category. The validation results from teacher responses were 93.1% in the Very Appropriate category, while student responses were 90.8% in the Very Appropriate category. Based on the percentage results from media experts, material experts, teacher responses and student responses, it can be concluded that the development of poop up book media with a problem based learning model in thematic learning on the theme of 7 objects, animals and plants around me which was developed by researchers at SD IT Al -Furqin for class I elementary school is included in the Very Suitable category to be applied or used as learning media in class I elementary school.